Multiscale Seismic Tomography - Zhao, Dapeng. (Springer Geophysics,, 2015)
This book on multiscale seismic tomography, written by one of the leaders in the field, is suitable for undergraduate and graduate students, researchers, and professionals in Earth and planetary sciences who need to broaden their horizons about seismotectonics, volcanism, and interior structure and dynamics of the Earth and Moon. It describes the state-of-the-art in seismic tomography, with emphasis on the new findings obtained by applying tomographic methods in local, regional, and global scales for understanding the generating mechanism of large and great earthquakes such as the 2011 Tohoku-oki earthquake (Mw 9.0), crustal and upper mantle structure, origin of active arc volcanoes and intraplate volcanoes including hotspots, heterogeneous structure of subduction zones, fate of subducting slabs, origin of mantle plumes, mantle convection, and deep Earth dynamics. The first lunar tomography and its implications for the mechanism of deep moonquakes and lunar evolution are also introduced.